Systematic review of hematophagous arthropods present in cattle in France - Prudhomme Jorian; Depaquit Jérôme; Fite Johanna; Quillery Elsa; Bouhsira Emilie; Liénard Emmanuel (Parasite, 2023)
The arrival of pathogens, whether zoonotic or not, can have a lasting effect on commercial livestock farms, with dramatic health, social and economic consequences. However, available data concerning the arthropod vectors present and circulating on livestock farms in France are still very imprecise, fragmentary, and scattered. In this context, we conducted a systematic review of the hematophagous arthropod species recorded on different types of cattle farms in mainland France (including Corsica). The used vector “groups” studied were biting flies, biting midges, black flies, fleas, horse flies, lice, louse flies, mosquitoes, sand flies, and ticks. A large number of documents were selected (N = 9,225), read (N = 1,047) and analyzed (N = 290), allowing us to provide distribution and abundance maps of different species of medical and veterinary interest according to literature data. Despite the large number of documents collected and analyzed, there are few data provided on cattle farm characteristics. Moreover, data on all arthropod groups lack numerical detail and are based on limited data in time and/or space. Therefore, they are not generalizable nor comparable. There is still little information on many vectors (and their pathogens) and still many unknowns for most studied groups. It appears necessary to provide new, updated and standardized data, collected in different geographical and climatological areas. Finally, this work highlights the lack of entomologists, funding, training and government support, leading to an increased risk of uncontrolled disease emergence in cattle herds.